ANALISIS RASIO KEUANGAN DENGAN MODEL ALTMAN Z-SCORE REVISI DALAM MEMPREDIKSI POTENSI KEBANGKRUTAN PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Putri, Khairunnisa Rafli Putri Rafli; Haryana, Gani Haryana; ', Makhdalena (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Ratio analysis can show or give an idea of ​​good or bad financial position that can lead to failure. In an effort to avoid failure or bankruptcy, managers need to know the company's financial condition or predict the potential bankruptcy of the company. This study was conducted to determine the outcome prediction of potential bankruptcy at the telecommunications company listed on the Stock Exchange which aims to commemorate the managerial company and protect investors and creditors in order not to lose. The population in this study are all telecommunication companies listed on the Stock Exchange that has the necessary data for 6 consecutive years the company as much as 5 to 2008 to 2013. Data used is secondary data obtained by the engineering documentation (annual reports and ICMD). Data analysis technique is descriptive analysis. The results obtained are among the five telecom companies surveyed, there are two potentially bankrupt company predicted that PT. Bakrie Telecome Tbk and PT. Smartfren Tbk, there is one company that is located in vulnerable areas (gray area), namely PT. Indosat Tbk and 2 Companies are at a healthy state, namely PT. XL Axiata Tbk and PT. Telecommunications Indonesia Tbk Key Words: Financial ratios, Altman Z-Score Revisions, Bankruptcy